Jessica Stockholder - Tillman, Lynne 1947-; Schwabsky, Barry; Cooke, Lynne 1952-; Celant, Germano 1940-2020; Stockholder, Jessica 1959- (Phaidon Press Ltd., 2018)
The definitive book on a creative force who continues to influence sculpture and installation art Jessica Stockholder has long broken down the boundaries between painting, sculpture, and architecture to explore the body in social and cultural space - using found objects intertwined with profusions of vivid colours. This revised, updated edition spotlights the extraordinary evolution of her career, and examines the pivotal role she has played in shaping some of the most fundamental ideas around which contemporary sculpture and painting revolve today
First edition published 1995 by Phaidon
First edition authored by Barry Schwabsky, Lynne Tillman, and Lynne Cooke
Keywords: Stockholder, Jessica / 1959-; Artists / United States / 20th century